Vedic Quality Standards of Aetiology, Symptoms, Spread, Prevention and Treatment of COVID-19: Ayurvedic Prospective - Rohit Mehta (Indian Journal of Integrative Medicine, 2022)
The pandemic COVID-19 was caused by severe acute respiratory syndrome coronavirus 2 (SARS CoV 2) and is unique in various facets. The earlier experience from the past severe acute respiratory syndrome (SARS) epidemics seems to be insufficient, and there is a need for better strategies in public health and medical care. Ayurveda is well known for its preventive and therapeutic aspects, but not getting utilized for prevention by the COVID-19 crisis may also be helpful as a supportive therapy with a current line of management. This paper aimed at understanding the almost 5000-year-old Ayurvedic perspective of prevention and treatment of COVID – 19 may be helpful to the world today. Sushruta Samhita and Charka Samhita are the major sources for data collection and also electronic databases PubMed, Google Scholar used in this review. Study selection based on Ayurvedic Literary review of Aetiology; Causative Factor; Symptoms; Biological weapon, Spread; Prevention and Intervention of COVID – 19.